Optic nerve hypoplasia, encephalopathy, and neurodevelopmental handicap. Issue 4 (April 1991) - Burke, J P; O'Keefe, M; Bowell, R
Abstract : Abnormalities of the central nervous system are frequently described in optic nerve hypoplasia. In a longitudinal study of 46 consecutive children (32 term, 14 preterm) with bilateral optic nerve hypoplasia 32 (69.5%) had associated neurodevelopmental handicap. Of these, 90% had structural central nervous system abnormalities on computed tomographic brain scans. Neurodevelopmental handicap occurred in 62.5% of the term and 86% of the preterm infants respectively. Term infants had a greater incidence of ventral developmental midline defects and proportionately fewer maternal and/or neonatal complications throughout pregnancy, while encephaloclastic lesions were commoner among the premature infants. An association of optic nerve hypoplasia with the twin transfusion syndrome and prenatal vascular encephalopathies is described.